Kertas Minor dari Timur: Koran Tribun Timur 2004-2016 - Sucipto, adi; Patahuddin, Patahuddin; Ridha, M. Rasyid (Pendidikan Sejarah Fakultas Ilmu Sosial Fakultas Ilmu Sosial, 2019)
A minor Paper from The East is a title that cover a daily newspaper in Makassar. The meaning of Paper in the rubric is the mention for Tribun Timur newspaper. While the Minor, because Tribun Timur newspaper is a newspaper that is fairly young or new, but can compete and even outperformed previously published newspaper. While From the East, because the Tribun Timur newspaper is in eastern Indonesia, namely Makassar. This research discusses about the birth process and the development of eastern tribune newspaper since 2004- 2016. The results showed that the Tribun Timur newspaper began to be initiated in 2003 and began to be published for the first time on 9 Februari 2004. Tribun Timur newspaper is under the auspices of PT.Bosowa Media Grafika. It is interesting from the background of the birth of the Tribun Timur newspaper experienced twice the turn of editor in chief, namely Uki M Kurdi and Dahlan Dahi. Oplah and readership progressed, the rubric also increased progressed, the rubric also increased to meet the information needs of the special community of Makassar. The Tribun Timur newspaper has a bigger thrill than the newspaper with the rubric citizen report. With the rubric, then the selection will be published. So the tapes from the Tribun Timur newspapervary because the people who send the news come from different backgrounds. This study uses historical research methods, namely heuristic (searching and collecting resources), source criticism, interpretation (interpretating sourse) and historiography (historical writing). Methods of data collection is done by doing literature research, field research (interviews) and documentation. The end of the research, drawn the conclusion that the birth of the Tribun Timur newspaper caused by the high population of Makassar, high buying power, Jusuf Kalla request to publish newspapers in Makassar and the lack of daily newspaper published in Makassar.